2012
DOI: 10.1016/j.ejphar.2011.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Riluzole and gabapentinoids activate glutamate transporters to facilitate glutamate-induced glutamate release from cultured astrocytes

Abstract: We have recently demonstrated that the glutamate transporter activator riluzole paradoxically enhanced glutamate-induced glutamate release from cultured astrocytes. We further showed that both riluzole and the α2δ subunit ligand gabapentin activated descending inhibition in rats by increasing glutamate receptor signaling in the locus coeruleus and hypothesized that these drugs share common mechanisms to enhance glutamate release from astrocytes. In the present study, we examined the effects of riluzole and gab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 31 publications
(56 reference statements)
0
38
0
1
Order By: Relevance
“…We previously demonstrated that gabapentin increases co-transport of Na + ions and glutamate via glutamate transporters, enhances the glutamate-induced intracellular Ca 2+ response via the reverse mode of Na + -Ca 2+ exchange, and by this mechanism facilitates glutamate release in cultured astrocytes (Yoshizumi et al, 2012a). Although GLT-1 may express in glutamatergic terminals in the LC (Medrano et al, 2013), the current study shows the in vivo relevance of this gabapentin’s action in astrocytes by demonstrating the role of GLT-1 in the gabapentin-induced glutamate increase in the LC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously demonstrated that gabapentin increases co-transport of Na + ions and glutamate via glutamate transporters, enhances the glutamate-induced intracellular Ca 2+ response via the reverse mode of Na + -Ca 2+ exchange, and by this mechanism facilitates glutamate release in cultured astrocytes (Yoshizumi et al, 2012a). Although GLT-1 may express in glutamatergic terminals in the LC (Medrano et al, 2013), the current study shows the in vivo relevance of this gabapentin’s action in astrocytes by demonstrating the role of GLT-1 in the gabapentin-induced glutamate increase in the LC.…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated in cultured astrocytes that gabapentin enhances Na + -glutamate co-transport through glutamate transporters, induces subsequent Ca 2+ influx via the reverse mode of Na + /Ca 2+ exchange, and thereby facilitates Ca 2+ -dependent glutamate release by glutamate (Yoshizumi et al, 2012a). However, the in vivo relevance of this action of gabapentin on astroglial glutamate regulation has not yet been tested in the LC.…”
Section: Introductionmentioning
confidence: 99%
“…Riluzole (Ril), currently used to treat amyotrophic lateral sclerosis, can significantly enhance glutamate clearance via an increase GLT1 expression and reduction in pre-synaptic release (Yoshizumi et al, 2012). The current study investigated whether Ril could prevent cognitive deficits associated with aging or experimentally-induced chronic neuroinflammation produced by infusion of LPS into the IV th ventricle and also restore the balance of pro- and anti-inflammatory genes and proteins.…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies suggest much of riluzoles neuroprotective effects could be mediated through the effects on GLT1 expression (Fumagalli et al 2008;Yoshizumi et al 2012). As also described earlier, multiple open label (nonplacebo controlled) clinical studies have found riluzole to be effective in the treatment of MDD, bipolar disorder (BPD), anxiety and obsessive-compulsive disorder (OCD) (Coric et al 2005;Pittenger et al 2008;Sanacora et al 2004).…”
Section: Treatments Targeting Glial and Glutamate Uptake Have Efficacmentioning
confidence: 89%